2006
DOI: 10.1080/14017430500339347
|View full text |Cite
|
Sign up to set email alerts
|

Sustained anti-β-adrenergic effect of melatonin in guinea pig heart papillary muscle

Abstract: Receptor-mediated immediate and sustained anti-ss-adrenergic effects of melatonin were demonstrated in contractile function. A role for NO in the response was indicated, while a role for PKC was not verified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…3C). It also has beneficial short‐term effects on myocardial postischemic recovery, which have been attributed to its free radical scavenging, antioxidant [for reviews see 21,24], antiadrenergic [31, 71, 72] as well as receptor‐mediated actions [22]. However, the mechanism by which chronic melatonin treatment improves ischemia/reperfusion injury remains under investigation.…”
Section: Discussionmentioning
confidence: 99%
“…3C). It also has beneficial short‐term effects on myocardial postischemic recovery, which have been attributed to its free radical scavenging, antioxidant [for reviews see 21,24], antiadrenergic [31, 71, 72] as well as receptor‐mediated actions [22]. However, the mechanism by which chronic melatonin treatment improves ischemia/reperfusion injury remains under investigation.…”
Section: Discussionmentioning
confidence: 99%
“…PKC, on the other hand, although involved in the anti‐adrenergic actions of melatonin (Table 5), had no effect on the melatonin‐induced reduction in infarct size as inhibition of its activation, had no effect on the melatonin‐induced reduction in infarct size. Similarly, an important role for PKC in the sustained anti‐β‐adrenergic effects of melatonin in papillary muscle contractility could not be shown [18].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies using chick retinal neurons indicated that melatonin inhibited forskolin-and dopamine-stimulated cAMP accumulation via its receptor and an inhibitory G-protein [16,17]. Evidence has also been presented for the anti-adrenergic actions of melatonin in the heart, based on its effects on contractility of isolated papillary muscles [18,19]. It was also shown that the EC50 for isoproterenol in papillary muscle was increased approximately 10-fold by melatonin [19].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the beneficial effects of exogenous melatonin on the heart in physiological conditions such as ageing as well as in pathophysiological conditions, for example hyperthyroidism (Ghosh et al 2007), cadmium-induced oxidative damage (Mukherjee et al 2011) and myocardial hypertrophy (Reiter et al 2010c) have been demonstrated. Besides its direct free radical scavenger and indirect antioxidant activity (Tengattini et al 2008), the contribution of MT receptors in the cardioprotective properties has also been emphasized (Arvola et al 2006, Sallinen et al 2007, Genade et al 2008, Grossini et al 2011, Lamont et al 2011. Besides its direct free radical scavenger and indirect antioxidant activity (Tengattini et al 2008), the contribution of MT receptors in the cardioprotective properties has also been emphasized (Arvola et al 2006, Sallinen et al 2007, Genade et al 2008, Grossini et al 2011, Lamont et al 2011.…”
Section: Cardiovascular Effects Of Melatoninmentioning
confidence: 99%
“…However, the mechanism of the actions of melatonin is still complex and not yet fully explored. Besides its direct free radical scavenger and indirect antioxidant activity (Tengattini et al 2008), the contribution of MT receptors in the cardioprotective properties has also been emphasized (Arvola et al 2006, Sallinen et al 2007, Genade et al 2008, Grossini et al 2011, Lamont et al 2011. Melatonin supplementation has largely been considered as a potential pharmacological agent in non-dipper and individuals with hypertension (Paulis & Simko 2007, Grossman et al 2011, Kozirog et al 2011.…”
Section: Cardiovascular Effects Of Melatoninmentioning
confidence: 99%